2012
DOI: 10.1182/blood-2011-11-393975
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes 5 years after response to rituximab therapy in children and adults with immune thrombocytopenia

Abstract: Treatments for immune thrombocytope-nic purpura (ITP) providing durable plate-let responses without continued dosing are limited. Whereas complete responses (CRs) to B-cell depletion in ITP usually last for 1 year in adults, partial responses (PRs) are less durable. Comparable data do not exist for children and 5-year outcomes are unavailable. Patients with ITP treated with rituximab who achieved CRs and PRs (platelets > 150 10 9 /L or 50-150 10 9 /L, respectively) were selected to be assessed for duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
245
2
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 298 publications
(264 citation statements)
references
References 47 publications
10
245
2
7
Order By: Relevance
“…Less impressive long-term outcome has been on the contrary reported by Patel et al [13] who analyzed data from 17 published studies which included 376 adults showing 5 years response rate only in 21%. This discrepancy could be at least partially explained by ours and Godeau's selection of patients with a lower degree of treatments received before rituximab [19].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Less impressive long-term outcome has been on the contrary reported by Patel et al [13] who analyzed data from 17 published studies which included 376 adults showing 5 years response rate only in 21%. This discrepancy could be at least partially explained by ours and Godeau's selection of patients with a lower degree of treatments received before rituximab [19].…”
Section: Discussionmentioning
confidence: 86%
“…Recently, Patel et al [13], analyzing data of 72 adults and 66 children with ITP who had at least an initial response to rituximab, calculated an estimated 5-years response rate of 21 and 30%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In France, based on the findings of a single-arm prospective study [4], RTX is now commonly used in persistent or chronic cases of adult ITP prior to splenectomy. Approximately 40-50% of patients treated with RTX at a standard dose achieve a complete response (CR) by 1 year [5] and 20% have a lasting response at 5 years [6]. The mechanisms of action of RTX to treat ITP remain speculative, although the removal of autoreactive B-cells is likely to play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, both in adults and in children, have shown a significant initial response in 40% of the cases and a long-lasting (5 y) response in 20-25% (19). For patients relapsing after rituximab therapy, splenectomy is often the only choice to overcome disease.…”
mentioning
confidence: 99%